Les vikings et leurs captifs Britanniques : entre violences infligées et violences fantasmées - Jean-Louis Parmentier (Criminocorpus)
Many stereotypes run through the historiography on Vikings and violence. This article proposes to reassess the fate of the captives during the Viking raids in the British Isles through a non-exhaustive corpus. The aim is to analyse the typology of captivity, the conditions of detention and the punishment inflicted by the Northmen: are the Scandinavians more violent than other peoples? Does being a prisoner of the Vikings necessarily imply terrible abuses ? Were the cruel acts cited in the sources actually practised ?